Design of a Construction Project Risk Monitoring and Control Framework through a Synthesis of Literature and Practice - Medina Winandyani; I Putu Artama Wiguna (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2026)
Construction projects operate under high uncertainty and remain vulnerable to cost, time, quality, and occupational safety issues. Although risk management is commonly applied, risk monitoring and control in practice often remain fragmented, with indicator tracking, follow-up actions, and reporting not always connected in a clear operational flow. This study aims to develop an initial design of a construction project risk monitoring and control framework that is practical, systematic, and easy to implement. The study adopts a design-study approach using secondary data derived from international standards and guidelines, scientific literature, and Indonesian construction risk management references, which were synthesized to identify the key process, information, and tool requirements of the framework. The proposed design integrates an iterative monitoring and control workflow, structured risk information including Early Warning Signs (EWS), Key Risk Indicator (KRI) grouping, metrics and thresholds, and action effectiveness evaluation, as well as semi-automated spreadsheet-based tools to support risk recording, evaluation, updating, and reporting. The contribution of this study lies in translating risk monitoring and control principles into a connected operational design that can support more consistent, traceable, and system-based project risk management practice. As a literature- and practice-based initial design, this framework is intended to serve as a foundation for further expert validation and implementation in construction projects.